Studi Kritik Pemahaman Agama dalam Muhammadiyah - Mahsyar Mahsyar; Ishak Ishak (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This study examines the understanding of religion in Muhammadiyah, the largest Islamic organization in Indonesia, with a focus on the methodology of thought grounded in the Qur'an and Sunnah. The research identifies the critical approach Muhammadiyah uses in understanding and practicing religious teachings, as well as how the organization responds to the challenges of the times through ijtihad and tajdid. The main concepts discussed include tawhid, worship, and sabilillah, as well as efforts to balance worldly and ukhrawi life. Through literature analysis, it was found that Muhammadiyah prioritizes rational and contextual understanding, encourages active participation in society, and rejects dogmatism. The results show that Muhammadiyah's approach contributes to social and educational development, and invites Muslims to integrate religious values with science. This research is expected to provide deeper insights into the dynamics of Muhammadiyah thought and its relevance in the modern context.